2022
DOI: 10.3390/nu14071523
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Lead Exposure and Bone Mineral Density in Childhood and Adolescence: Results from NHANES 1999–2006 and 2011–2018

Abstract: There are few studies on lead’s effect on bone mineral density (BMD) in childhood. In this study, we examined the association between lead exposure and BMD among 13,951 children and adolescents aged 8–19 years from NHANES 1999–2006 and 2011–2018. The whole blood lead levels (BLLs) were used as lead exposure biomarkers, and total BMD, subtotal BMD, lumbar spine BMD and limb BMD were used as outcome variables. The survey weighted multivariable generalized additive models (GAMs) with smoothing terms were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Meanwhile, Cho et al found that children with a mean blood lead level of 1.9 μg/dl had symptoms of attention deficit hyperactivity disorder (ADHD) ( 35 ). An N-shaped curve was found between BLL and total BMD(bone mineral density), subtotal BMD and limb BMD for males and females at low-dose lead exposure (0.84 ug/dl) ( 36 ). In addition, when studying the relationship between blood lead and cardiovascular risk factors, Xu ( 24 ) found a positive correlation between BLL (geometric mean of 1.17 ug/dl) and serum LDL-C (low-density lipoprotein cholesterol, a biomarker associated with cardiovascular disease) in American adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Cho et al found that children with a mean blood lead level of 1.9 μg/dl had symptoms of attention deficit hyperactivity disorder (ADHD) ( 35 ). An N-shaped curve was found between BLL and total BMD(bone mineral density), subtotal BMD and limb BMD for males and females at low-dose lead exposure (0.84 ug/dl) ( 36 ). In addition, when studying the relationship between blood lead and cardiovascular risk factors, Xu ( 24 ) found a positive correlation between BLL (geometric mean of 1.17 ug/dl) and serum LDL-C (low-density lipoprotein cholesterol, a biomarker associated with cardiovascular disease) in American adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Other covariates. Other covariates were chosen based on the published studies [8,24,25]. The variance inflation factor (VIF) was used to detect co-linearity between multiple variables.…”
Section: Plos Onementioning
confidence: 99%
“…Based on previous studies (18,(22)(23)(24), confounders that may influence BMD were chosen to eliminate potential effects on the results. We also performed a multicollinearity analysis of these covariates and did not find the presence of multicollinearity.…”
Section: Variablesmentioning
confidence: 99%
“…However, it recruited smaller samples, which may result in an unreliable conclusion (17). A recent study conducted by Li et al (18) showed an N-shaped curve association between BLL and BMD in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%